Critique of Salah Fadl’s "Approach of Realism in Literary Creativity" - Fatima Parchekani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Using a series of criteria, literary criticism is concerned with the study of literary works from the start explaining the works, their elements and concepts, and clarifying their weaknesses and strengths; ultimately, it helps to improve the quality of the work. These attempts of division of critical theories under literary doctrines can be considered as good examples, and the book "Approach of Realism in Literary Creativity" by Salah Fadl fits the critique in this model. This research attempts to answer a fundamental dilemma: To what extent did this book succeed in completing the explanation of status and criticism of the realist doctrine? The analytical methodological method shows that the book has had great success in explaining the reality theories, whether in form or content, although there are some shortcomings such as the lack of concrete and tangible evidence in the literary texts.